2001
DOI: 10.1055/s-2001-16214
|View full text |Cite
|
Sign up to set email alerts
|

Diamond Stents for Palliation of Malignant Bile Duct Obstruction: A Prospective Multicenter Evaluation

Abstract: The Diamond stent compares favorably with other biliary metal stents for patients requiring biliary drainage of malignant jaundice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…[10][11][12] However, despite improvements in materials and stent design, problems remain, as exemplified by the 13% to 44% reintervention rate attributed to stent failure with SEMSs. [13][14][15][16] A number of factors have been suggested to explain this relatively high failure rate, including epithelial hyperplasia, tumor ingrowth and overgrowth, dislocation, debris formation, and clot accumulation. 1,17,18 To better counteract tumor ingrowth in uncovered SEMSs (uSEMSs), covered SEMSs (cSEMSs) were developed by placing a thin nonporous membrane on the inside of the metal mesh.…”
mentioning
confidence: 98%
“…[10][11][12] However, despite improvements in materials and stent design, problems remain, as exemplified by the 13% to 44% reintervention rate attributed to stent failure with SEMSs. [13][14][15][16] A number of factors have been suggested to explain this relatively high failure rate, including epithelial hyperplasia, tumor ingrowth and overgrowth, dislocation, debris formation, and clot accumulation. 1,17,18 To better counteract tumor ingrowth in uncovered SEMSs (uSEMSs), covered SEMSs (cSEMSs) were developed by placing a thin nonporous membrane on the inside of the metal mesh.…”
mentioning
confidence: 98%
“…Although aIl studies used the uncovered WaIlstent® SEMS, recent RCTs suggested aIl uncovered stents are equally effective [135,136]. It is also clear that patients treated with uncovered SEMS are less likely to be hospitalized and require endoscopie reintervention due to stent dysfunction; it certainly has an economical impact that is related to the local standards and costs.…”
Section: Self-expandable Metal Stentsmentioning
confidence: 99%
“…Nonetheless, SEMS do eventually occlude in 19-40 % of patients [3][4][5]. The duration of SEMS patency has remained largely unchanged in spite of modifications in stent composition and the addition of a plastic coating [7][8][9]. Thus, a clear need exists for technologic improvements that minimize stent occlusion.…”
mentioning
confidence: 99%